2015
DOI: 10.1038/cddis.2015.263
|View full text |Cite
|
Sign up to set email alerts
|

Early effects of the antineoplastic agent salinomycin on mitochondrial function

Abstract: Salinomycin, isolated from Streptomyces albus, displays antimicrobial activity. Recently, a large-scale screening approach identified salinomycin and nigericin as selective apoptosis inducers of cancer stem cells. Growing evidence suggests that salinomycin is able to kill different types of non-stem tumor cells that usually display resistance to common therapeutic approaches, but the mechanism of action of this molecule is still poorly understood. Since salinomycin has been suggested to act as a K+ ionophore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 62 publications
1
56
0
Order By: Relevance
“…Similarly, metformin, which has complex I inhibitory effects, induced rapid apoptosis of pancreatic CSCs [21]. Salinomycin, an antibiotic that was recently identified as a selective inhibitor of CSCs [22] has been shown to reduce cell survival, at least partially, by impairing mitochondrial bioenergetic performance [23]. Finally, pyrvinium pamoate, an FDA-approved anti-parasitic agent, behaves as an OXPHOS inhibitor targeting mitochondrial complex II and efficiently prevents mammosphere formation in the nano-molar range, with an IC-50 of 50 nM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, metformin, which has complex I inhibitory effects, induced rapid apoptosis of pancreatic CSCs [21]. Salinomycin, an antibiotic that was recently identified as a selective inhibitor of CSCs [22] has been shown to reduce cell survival, at least partially, by impairing mitochondrial bioenergetic performance [23]. Finally, pyrvinium pamoate, an FDA-approved anti-parasitic agent, behaves as an OXPHOS inhibitor targeting mitochondrial complex II and efficiently prevents mammosphere formation in the nano-molar range, with an IC-50 of 50 nM [18].…”
Section: Introductionmentioning
confidence: 99%
“…30 However, its mode of action is distinct to that of valinomycin and instead of depolarizing the IMM, salinomycin induces its transient hyperpolarization. 30,31 In contrast to valinomycin, salinomycin increases the efflux of K + from the mitochondrion by catalyzing their electroneutral exchange against protons and subsequently modifies the pH gradient across the IMM. 31 The acidification of the mitochondrial matrix impairs mitochondrial respiration and thus, limits the generation of ATP, eventually leading to mitochondrial failure and activation of the mitochondrial removal process.…”
Section: Mitochondrial Toxinsmentioning
confidence: 99%
“…30,31 In contrast to valinomycin, salinomycin increases the efflux of K + from the mitochondrion by catalyzing their electroneutral exchange against protons and subsequently modifies the pH gradient across the IMM. 31 The acidification of the mitochondrial matrix impairs mitochondrial respiration and thus, limits the generation of ATP, eventually leading to mitochondrial failure and activation of the mitochondrial removal process. 30,31 Another example is the antibiotic antimycin A that elicits a mitochondria-targeted autophagic response by inhibiting the respiratory complex III and leading to increased levels of reactive oxygen species (ROS) ( Table 1).…”
Section: Mitochondrial Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIG is a K + /H + ionophore derived from S. hygroscopicus that has been recently shown to overcome multidrug resistance of cancer cells 27 and to target CSCs. 15,[28][29][30] However, a recent study found that stem-like ovarian cancer cells expressing high levels of ABC drug transporters were largely resistant to ionophore antibiotics (IAs) such as salinomycin and NIG suggesting that IAs alone cannot eliminate certain CSLCs. 31,32 NIG also inhibits cellular processes associated with increased stemness such as metastasis and epithelial mesenchymal transition (EMT) in colorectal 16 and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%